ANALYSIS OF SEAGRASS DENSITY RELATION TO MACROZOOBENTHIC ABUNDANCE IN WATERS OF BINTAN STRAIT PENGUJAN VILLAGE BINTAN REGENCY OF RIAU PROVINCE - Junaidi '; Zulkifli '; Thamrin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in October 2016 in the waters of Bintan Strait of Desa Pengujan of Bintan Regency of Kepulauan Riau Province. The purpose of this study was to determine the level of seagrass density, macrozoobenthic abundance and seagrass density relation to macrozoobenthic abundance in waters of Bintan Strait of Desa Pengujan. This research uses survey method and location of observation determined by Purposive sampling.The location of the observation is divided into 3 stations, the first station is adjacent to the fish seed area, the second station is between the fish seed and magrove area and the third station is adjacent to the magrove area.The number of seagrasses found in 4 species are: Enhalus acoroides, Halopila minor, Halodule uninervis, and Thalassia hemprichii, which have very high seagrass density, and identified macrozoobenthos species are 3 classes: Gastropoda, Bivalva and Asteroidea, consisting of 13 species at 3 observation stations, 7 species of gastopod class, 5 species of bivalve class and 1 species of Asteroidea class, with abundant levels of abundance. The density of seagrass to makrozoobentos abundance of 18%, while 82% influenced by other environmental factors such as physical parameters, chemistry and organic matter content in the waters.Keyword : Pengujan village, Seagrass, Macrozoobenthos